Effects of a Dual Space Inquiry Based E-Module on Students' Learning Outcomes in Work and Energy - Nabilah Zhahirah; Fuja Novitra; Hufri Hufri; Hayyu Yumna (Universitas Negeri Padang in collaboration with Association of Mathematics and Natural Sciences Institution for Education of Teaching Staff Indonesia (AMLI), 2026)
Learning outcomes are one indicator of successful learning, influenced by the use of appropriate instructional models and teaching materials. However, teaching physics on the topic of Work and Energy still faces various challenges, particularly in helping students understand abstract concepts. One approach to addressing this issue is through the use of Dual Space Inquiry-based e-modules that integrate inquiry activities in both digital and real-world learning environments. This study aims to analyze the effect of Dual Space Inquiry-based e-modules on student learning outcomes in the topic of Work and Energy. This study employed a quantitative method using a posttest-only control group design. The sample consisted of 76 tenth-grade students at SMA N 4 Padang, divided into an experimental class and a control class. Learning outcome data were obtained through a posttest and analyzed using appropriate statistical tests. The results showed that students who learned using the Dual Space Inquiry-based e-module achieved better learning outcomes than those in the control class. These findings indicate that the Dual Space Inquiry-based e-module can serve as an innovative teaching resource that supports physics learning and helps improve students’ learning outcomes in the topic of Work and Energy.